Direct-Contact Evaporation Using Different Refrigerants: A Review - Hayder, Safaa Hafedh; Danook, Suad Hassan; Sultan, Hussein Sadiq (Basrah Journal for Engineering Sciences, 2020)
The direct-contact evaporation method is characterized by its effectiveness in applications of heat exchangers, especially in cooling systems, due to the absence of any heat resistors that prevent the transfer of heat between the cold and hot medium. The direct contact heat transfer depends mainly on how quickly the heat is taken by the bubbles of the evaporative refrigerant from the liquid and the increase in its volume up to the top of the heat exchanger, which is usually a cylindrical liquid column so that the temperature drop therein is uniform and even. There is much research on the method of heat transfer by direct contact. In this research, we collected and summarized most of the theoretical and practical researches that examined this method with the most important findings.